An annotated checklist of the Arcella (Arcellidae) from littoral zone of Paranoá lake-Brazil, with a pictorial key - Mariana Lessa Carneiro da Silva; Elisangela Reis Rangel; Fabio Amodêo Lansac-Tôha; Leilane Talita Fatoreto Schwind; Ciro Yoshio Joko (Acta Scientiarum. Biological Sciences, 2016)
The pictorial key contributes to taxonomic analysis, as it lists the species found in a given environment, and points out the morphological characteristics that differs one specific taxon from the others. Arcellidae Ehrenberg, 1830 is one of the testate amoebae families with highest representativity in terms of richness and abundance, including three genera, that Arcella shows greater dispersion in different types of aquatic biotopes. The zooplankton community in the Paranoá Lake has been extensively studied over the decades. However, there are no studies on testate amoebae in this environment. The study aimed to develop a pictorial key to help in the identification of Arcella in the Paranoá Lake. Samples were taken with plankton net at 13 sites in the littoral zone of the lake. The elaboration of the key was based on morphological characteristics of the shell and pseudostoma of the individuals. There were identified 23 taxa, 16 species and seven subspecies. Two species with low incidence in Brazil were recorded (Arcella catinus and Arcella rota). The species richness was higher than the records published to date in Brazil, thus demonstrating the relevance of the data and the applicability of this pictorial key in other studies both in the Paranoá Lake, as in other regions.